2021
DOI: 10.3389/fpls.2021.685488
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genomic Selection at the Early Stage of Breeding Pipeline in Tropical Maize

Abstract: In maize, doubled haploid (DH) line production capacity of large-sized maize breeding programs often exceeds the capacity to phenotypically evaluate the complete set of testcross candidates in multi-location trials. The ability to partially select DH lines based on genotypic data while maintaining or improving genetic gains for key traits using phenotypic selection can result in significant resource savings. The present study aimed to evaluate genomic selection (GS) prediction scenarios for grain yield and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…It also showed the potential to select high-breeding value individuals from Frontiers in Genetics frontiersin.org early-generation populations without extensive field testing. GS has been shown effective in wheat (Bonnett et al, 2022), maize (Beyene et al, 2021), barley (Sallam et al, 2015), and even rice (Xu et al, 2021). In our study, we also found that genetic gain per unit of time is much faster in the GS strategy than in the conventional selection methods.…”
Section: Discussionsupporting
confidence: 70%
“…It also showed the potential to select high-breeding value individuals from Frontiers in Genetics frontiersin.org early-generation populations without extensive field testing. GS has been shown effective in wheat (Bonnett et al, 2022), maize (Beyene et al, 2021), barley (Sallam et al, 2015), and even rice (Xu et al, 2021). In our study, we also found that genetic gain per unit of time is much faster in the GS strategy than in the conventional selection methods.…”
Section: Discussionsupporting
confidence: 70%
“…GS in tropical maize for various traits of interest revealed moderate to high prediction accuracies in several studies (Azmach et al 2018 ; Beyene et al 2019 ; Crossa et al 2014 ; Gowda et al 2021 ). The relative merits of GS over phenotypic selection influence its widespread application in breeding programs ( Beyene et al 2019 , 2021 ; Kibe et al 2020a ). Moderate to high accuracies observed in this study for the bi-parental populations and IMAS panel offer promise in breeding for quality traits in tropical maize.…”
Section: Discussionmentioning
confidence: 99%
“…High genetic gain can be achieved for complex traits by integrating modern tools into maize breeding [ 85 , 86 ]. With several genotyping service providers available with a lower cost per sample and availability of advanced statistical models, genomic prediction is routinely applied in maize for several quantitative traits [ 24 , 85 , 86 ]. In the present study, we compared the prediction accuracies under WW and WS conditions ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%